STRATEGI PEMASARAN KEDELAI (Glycine max L) PADA KELOMPOK TANI PANTUN WANGI DI DESA BENGKEL - Alfrinto Rison Ngongo; Nyoman Utari Vipriyanti; Cening Kardi, (AGRIFARM (Jurnal Agribisnis dan Sosial Ekonomi Pertanian), 2023)
This study aims to determine the internal and external factors of soybean marketing and formulate a marketing strategy for soybeans in the Pantun Wangi Farmer Group in Bengkel Village, Kediri District, Tabanan Regency. Determination of research location is determined by census. The number of respondents in the study amounted to 30. The method used in determining respondents was the census method. The analytical method used in this study is to use the SWOT analysis method. Based on the SWOT analysis in this study resulted in five factors of strengths, weaknesses, opportunities and threats. Based on the SWOT diagram, it is known that the soybean marketing strategy is in quadrant I which means that the strategy that can be applied to develop soybean agribusiness is to use strengths and take advantage of existing opportunities. Three strategies that can be applied to develop soybeans are developing available resources, increasing cooperation between the government and farmers, and developing marketing management